The Role of CD276 in Cancers - Liu, Shengzhuo; Liang, Jiayu; Liu, Zhihong; Zhang, Chi; Wang, Yang; Watson, Alice Helen; Zhou, Chuan; Zhang, Fan; Wu, Kan; Zhang, Fuxun; Lu, Yiping; Wang, Xianding (Frontiers in Oncology, 2021)
Abstract: Objective:  Aberrant expression of the immune checkpoint molecule, CD276, also known as B7-H3, is associated with tumorigenesis. In this review, we aim to comprehensively describe the role of CD276 in malignancies and its potential therapeutic effect. Data sources: Database including PubMed, EMbase, Cochrane Library, CNKI and Clinical Trails.gov were searched for eligible studies and reviews. Study selection: Original studies and review articles on the topic of CD276 in tumors were retrieved. Results: CD276 is an immune checkpoint molecule in the epithelial mesenchymal transition (EMT) pathway. In this review, we evaluated the available evidence on the expression and regulation of CD276. We also assessed the role of CD276 within the immune micro-environment, effect on tumor progression and the potential therapeutic effect of CD276 targeted therapy for malignancies. Conclusion: CD276 plays an essential role in cell proliferation, invasion and migration in malignancies. Results from most recent studies indicate CD276 could be a promising therapeutic target for malignant tumors.